Information literacy: a factor to overcome the barriers of innovation in the context of industry 4.0 - Capinzaiki Ottonicar, Selma Leticia [UNESP]; Nascimento, Natalia Marinho da [UNESP]; Biaggi, Camila de [UNESP]; Mosconi, Elaine Paiva (Univ Brasilia, Dept Ciencia Informacao, 2020)
This paper aims to discuss how information literacy can support businesses to overcome the barriers of the innovation process in the context of industry 4.0. The focus is to help professionals to overcome innovation barriers through information literacy. A bibliographic review is used in the methodology to demonstrate the gap in the literature about information literacy and Industry 4.0. Furthermore, a chart is developed to explain the relationship of these concepts. In the end, a conceptual model is proposed to help professionals to overcome the factors that hamper innovation in businesses, specially the organizations which has already adopted the technology of Industry 4.0. As conclusion, competitiveness depends on information truthfulness and innovation quality. Information literacy is an important tool to overcome the barriers that hamper innovation, since in the context of Industry 4.0 individuals need to become more skilled to interpret information.
Keywords: information literacy; innovation; industry 4.0; literature review; business competitiveness